HUBUNGAN ANTARA KONSEP DIRI DENGAN KEMANDIRIAN ANAK USIA 4-5 TAHUN DI PAUD BENING KIDS KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rahmawati, Sri; Novianti, Ria; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the relationship between self-concept and the independence of childreen aged 4-5 years at the PAUD Bening Kids sub-district of Tenayan Raya pekanbaru city. The sampling taker tool uses a saturated sample technique, the subject set in this study were 34 people aged 4-5 years. Data collection of this study in the form of primary data, using the observation sheet. Data analysis techniques using t-test using the program SPSS 18.0. the research hypothesis is that there is a relationship between self-concept and the independence of childreen aged 4-5 years at the PAUD Bening Kids sub-district of Tenayan Raya Pekanbaru City based on data analysis it is known t count = 9,434 > t table = 0,344 with Sig. (2-tailed) = 0.000. because Sig < 0,05 it can be concluded that there is a relationship between self-concept and children’s independence. And there is a relationship between self-concept and the independence of children aged 4-5 years at the PAUD Bening Kids sub-district of Tenayan Raya Pekanbaru city for 73,6%.Key words: Self-Concept, Children’s Independence